(untitled) (Research, Society and Development, 2021)
During the COVID pandemic, the use of technical biosafety terms used in the health field and in research laboratories has become much more frequent. However, many of these Portuguese terms do not yet exist in the Brazilian Sign Language - Libras, which hinders comprehension of the terms and brings risks to health of deaf people and makes communication with health professionals almost impeditive. Thus, the creation of a bilingual thesaurus (Libras-Portuguese) in the area of biosafety is essential. This research aims to present a bilingual manual with new terms in Libras, using videos, as a tool to allow communication and training for deaf and health professionals. Methodology: The selection of terms for the manual was based on media, newspapers and specialized literature using the descriptive systematic review method. 10 themes were selected for the elaboration of the manual’s explanatory videos. Validation of the new words in Libras was carried out with a research group from INES (National Institute of Education for the Deaf). The videos were made available online at “Biocinais” platform. Result: We observed a high number of access to videos that explain the concepts of biosafety, PPE and CPE. Conclusion: The preliminary results demonstrate that the construction of manuals that facilitate the understanding of deaf people about biosafety and their communication with health professionals is extremely important, since there is little source of information on this topic for the deaf, and more works like this should be encouraged.